The Design of One-Dimensional Motion and Two-Dimensional Motion Learning Media Using Digital Camera and Tracker-Based Air Track - Fransisca Indra Dewi; Nur Aji Wibowo; Debora Natalia Sudjito; Ferdy Rondonuwu (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This research describes the results of the development of 2D air track tools designed for one and two-dimensional motion experiments with small frictional forces. Friction is minimized by using wind gusts through small holes made in all parts of the runway. Motion detection devices used are digital cameras and trackers. Digital cameras are used to record the motion of objects on a platform in the form of video with a specific frame-rate. Tracker is used to analyzing videos that contain information about object motion. This tool has been tested on one-dimensional motion, that is, an object that slides over an inclined plane and two-dimensional motion in the case of a collision of two objects. In the case of one-dimensional position graphs against time can be displayed, the instantaneous velocity and average and acceleration can be accurately determined. In the case of the collision of two objects, the position graph against time can also be displayed for each object before and after the collision. The velocity vector can be determined accurately so that the law of conservation of momentum and kinetic energy can be verified. One and two-dimensional motion are the concepts that underlie almost all other concepts in physics. Therefore one and two-dimensional motion experiments are important to build students’ experiences of the concept. Thus 2D air track platform based on digital cameras and Tracker software can be used as a physics learning media on motion kinematics materials that can display various kinematics graphs so that information about motion is complete.